Josep Lluís Blasco, politician and philosopher - Gómez Soler, Sílvia (Journal of Catalan Intellectual History, 2012)
Josep-Lluís Blasco (1940-2003) was an inspired ideologist to the political parties embodying nationalist and leftist positions in the Valencian Country. In regard to Philosophy, Blasco awoke an interest in analytic philosophy and took part in one of the most successful projects the Faculty of Philosophy of Valencia ever endeavored: the international symposia on Logic and Philosophy of Science and the publication of the journal Teorema. His work counts as one of the most solid contributions our culture has yielded within the field of Epistemology. key words: Josep-Lluís Blasco, Catalan Philosophy, Analytical Philosophy, Epistemology.